STUDI MENGENAI STATUS GIZI BALITA - Syarifa Amalia Alhamid; Bunga Tiara Carolin; Rosmawaty Lubis (JKM (Jurnal Kebidanan Malahayati), 2021)
ABSTRACT: A STUDY OF THE NUTRITIONAL STATUS OF TODDLERS  Background: Nutrition is a very important part of the growth and development of toddlers which is related to health and intelligence. In 2019, the prevalence of malnutrition in Bula District Seram was 10.2%, malnutrition was 4.3% and over nutrition was 5.1%, where the incidence rate was increased from the previous year.Objective: To determine the factors related to the nutritional status of toddlers in the Bula Health Center, East Seram District, Maluku Province.Methodology: This study is a cross sectional correlation study. The samples in the study were all women who had children aged 1-5 years who visited the Bula Health Center, East Seram Regency, Maluku Province in 2020 which consisted 76 toddlers. The research instrument was a questionnaire, data analysis using the chi square test.Results: the results showed that malnourished toddlers were 59.2%, women with poor knowledge were 76.3%, women who had low level education were 63.2%, women with low family income were 72.4%, women who did not work were 55.3%, women who did not provide breast feeding was 71.1% and toddlers who had the history of infectious diseases were 71.1%. The bivariate results obtained knowledge (p=0,022), education (p=0,048), income (p=0,002), occupation (p=0,088), history of breastfeeding (p=0,001) and a history of infectious diseases (p=0,020).Conclusions: There is a relationship between knowledge, education, family income, history of breastfeeding, and a history of infectious diseases with the nutritional status of toddlers.Suggestions: It is hoped that health workers can provide education about nutrition to mothers, so that they could pay more attention to the nutritional status of their toddlers.Keywords: Toddler, Bula Health Centre, Nutritional Status ABSTRAK Latar belakang: Gizi menjadi bagian sangat penting dalam pertumbuhan dan perkembangan balita yang didalamnya memiliki keterkaitan yang erat hubungannya dengan kesehatan dan kecerdasan. Pada tahun 2019 di Puskesmas Bula Kabupaten Seram prevelnsi gizi  kurang sebesar 10,2%, Gizi Buruk 4,3% dan gizi lebih 5,1% dimana angka kejadian ini menigkat dari tahun sebelumnya.Tujuan: Mengetahui faktor yang berhubungan dengan status gizi balita di Wilayah Puskesmas Bula Kabupaten Seram Bagian Timur Provinsi Maluku.Metodologi: Penelitian ini adalah penelitian korelasi dengan cross sectional. Sampel dalam penelitian adalah semua ibu yang mempunyai balita usia 1-5 tahun yang berkunjung ke Puskesmas Bula Kabupaten Seram Bagian Timur Provinsi Maluku tahun 2020 berjumlah 76 balita. Instrumen penelitian adalah kuesioner, analisis data menggunakan uji chi square.Hasil penelitian: Pada hasil didapatkan balita gizi kurang (59,2%), ibu berpengetahuan kurang baik (76,3%), ibu berpendidikan rendah (63,2%). pendapatan keluarga rendah (72,4%), ibu yang tidak berkerja (55,3%), ibu yang tidak memberikan ASI (71,1%) dan balita yang memiliki riwayat penyakit infeksi (71,1%). Hasil bivariat didapatkan pengetahuan (p=0,022), pendidikan (p=0,048), pendapatan (p=0,002), pekerjaan (p=0,088), riwayat ASI (p=0,001) dan riwayat penyakit infeksi (p=0,020).Kesimpulan: Terdapat hubungan antara pengetahuan, pendidikan, pendapatan keluarga, riwayat ASI, dan riwayat penyakit infeksi dengan status gizi balita.Saran: Diharapkan kepada petugas kesehatan dapat memberikan edukasi mengenai gizi kepada ibu agar lebih memperhatikan status gizi balitanya. Kata Kunci: Balita, Puskesmas Bula, Status gizi